Thermoelectric transport properties of n-type tin sulfide. (September 2019) - Hu, Xuegao; He, Wenke; Wang, Dongyang; Yuan, Bifei; Huang, Zhiwei; Zhao, Li-Dong
Abstract: In this paper, n -type polycrystalline tin sulfide (SnS) was firstly synthesized through optimizing Br doping. Comparably, n -type crystalline SnS with optimized Br doping was prepared, which exhibits better thermoelectric performance than that in polycrystalline SnS over a wide temperature range due to higher carrier mobility. A maximum average dimensionless figure of merit ( ZT ) ~0.08 at 300–823 K was achieved in n -type SnS crystals, which is 2 times higher than that in polycrystalline SnS. This work provides an effective strategy to enhance performance of earth-abundant and low-cost n -type SnS through electron-doping, higher performance can be expected in crystalline form. Graphical abstract: N -type SnS crystals with layered structure exhibits higher thermoelectric performance than that in SnS polycrystals due to higher carrier mobility. A maximum ZT ~0.12 at 823 K and an average ZT ave ~0.08 at 300–823 K were achieved in n -type SnS crystals.Unlabelled Image